Components of smartphone cognitive-behavioural therapy for subthreshold depression among 1093 university students: a factorial trial. Issue Volume 25:Issue e1(2022) (16th May 2022) - Sakata, Masatsugu; Toyomoto, Rie; Yoshida, Kazufumi; Luo, Yan; Nakagami, Yukako; Uwatoko, Teruhisa; Shimamoto, Tomonari; Tajika, Aran; Suga, Hidemichi; Ito, Hiroshi; Sumi, Michihisa; Muto, Takashi; et al.
Abstract : Background: Internet-based cognitive-behavioural therapy (iCBT) is effective for subthreshold depression. However, which skills provided in iCBT packages are more effective than others is unclear. Such knowledge can inform construction of more effective and efficient iCBT programmes. Objective: To examine the efficacy of five components of iCBT for subthreshold depression. Methods: We conducted an factorial trial using a smartphone app, randomly allocating presence or absence of five iCBT skills including self-monitoring, behavioural activation (BA), cognitive restructuring (CR), assertiveness training (AT) and problem-solving. Participants were university students with subthreshold depression. The primary outcome was the change on the Patient Health Questionnaire-9 (PHQ-9) from baseline to week 8. Secondary outcomes included changes in CBT skills. Findings: We randomised a total of 1093 participants. In all groups, participants had a significant PHQ-9 reduction from baseline to week 8. Depression reduction was not significantly different between presence or absence of any component, with corresponding standardised mean differences (negative values indicate specific efficacy in favour of the component) ranging between −0.04 (95% CI −0.16 to 0.08) for BA and 0.06 (95% CI −0.06 to 0.18) for AT. Specific CBT skill improvements were noted for CR and AT but not for the others. Conclusions: There was significant reduction in depression for all participants regardless of the presence and absence of the examined iCBT components. Clinical implication: We cannot yet make evidence-based recommendations for specific iCBT components. We suggest that future iCBT optimisation research should scrutinise the amount and structure of components to examine. Trial registration number: UMINCTR-000031307.